Usaha Mikro, Kecil dan Menengah Indonesia Menuju ASEAN Economic Community - Dewa Gede Sudika Mangku (Faculty of Law, Universitas Wijayakusuma, 2019)
Indonesia and all ASEAN members are getting ready to welcome and imple-ment the ASEAN Economic Community. MSMEs that are the drivers of the national economy must be able to take this golden opportunity for the national interests of Indonesia and not the other way around. we become the markets of other member countries. of course this is a particular challenge for national MSMEs to face the ASEAN Single Market. MSMEs must maintain and enhance competitiveness as a creative and innovative industry. In addition. MSMEs must also improve the standards. design and quality of products so that they are in accordance with ASEAN provisions by looking at the provisions of ISO 26000 for Green Products. The Indonesian government must work hard to help MSMEs experiencing barriers such as facilitating the provision of access to credit in banks. providing entrepreneurship training. increasing access to funding for MSMEs. facilitating financing for new entrepreneurs.Keywords: ASEAN Economic Community, Micro, Small and Medium Enterprises, Single Market